Utilization of Aerial Photograph and Geographic Information System for Deposit Measurement of Wuryantoro Watershed, Wonogiri - Sugiharto Budi Santoso (Forum Geografi, 2003)
This research is carried out in Wuryantoro Watershed, Wonogiri, Central Java. The goal of this study is to examine the remote sensing tehnology capability to obtain the parameters of the physical data of land in the prediction of sediment yield. The approach used in landscape with the land unit as mapping unit by using MUSLE (Modified Universal Soil Loss Equation) model. The data analysis used the infrared aerial photo interpretation, which is combined   by Geographical Information Systems (GIS). Infrared aerial photo on scale 1 : 10.000 in 1991 is used as primary source of data to obtain the parameters of physical data of land. The data analysis uses the Geographical Information Systems. The prediction of the sediment yield is not done directly. First, predicated the runoff characteristi, which contains of runoff coeficient, runoff volume and peak discharge. Then the runoff charateristic with other influential factors (slope, soil, and land cover and conservation practice) are used to predict the sediment yield. The result of the prediction is tested by comparing them with the data of field measurenment result. The accuracy of the result of aerial photo interpretation for prediction sediment yield is 89.45%.